2010
DOI: 10.1074/jbc.m109.069955
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation Anergy in Human Intestinal Macrophages Is Due to Smad-induced IκBα Expression and NF-κB Inactivation

Abstract: Human intestinal macrophages contribute to tissue homeostasis in noninflamed mucosa through profound down-regulation of pro-inflammatory cytokine release. Here, we show that this down-regulation extends to Toll-like receptor (TLR)-induced cytokine release, as intestinal macrophages expressed TLR3–TLR9 but did not release cytokines in response to TLR-specific ligands. Likely contributing to this unique functional profile, intestinal macrophages expressed markedly down-regulated adapter proteins MyD88 and Toll i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
204
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 162 publications
(218 citation statements)
references
References 43 publications
12
204
2
Order By: Relevance
“…The ligands for each of these receptors are highly abundant in the intestine and in vitro studies have shown that some of these ligands can drive Mj differentiation into a pathway similar to that seen in the intestine. Thus IL-10 produces TLR unresponsiveness in Mjs, while TGF-b derived from intestinal stroma inhibits NF-kB signalling in blood monocytes and recently has been suggested to cause the refractory state seen in resident mucosal Mjs [37,40]. Similar polarising roles for IL-10 and TGF-b have been described for the M2-like subset of regulatory Mjs discussed above [30].…”
Section: How Are Intestinal Macrophages Kept Inert?mentioning
confidence: 57%
See 2 more Smart Citations
“…The ligands for each of these receptors are highly abundant in the intestine and in vitro studies have shown that some of these ligands can drive Mj differentiation into a pathway similar to that seen in the intestine. Thus IL-10 produces TLR unresponsiveness in Mjs, while TGF-b derived from intestinal stroma inhibits NF-kB signalling in blood monocytes and recently has been suggested to cause the refractory state seen in resident mucosal Mjs [37,40]. Similar polarising roles for IL-10 and TGF-b have been described for the M2-like subset of regulatory Mjs discussed above [30].…”
Section: How Are Intestinal Macrophages Kept Inert?mentioning
confidence: 57%
“…Early studies focusing on human intestinal Mjs attributed the unresponsiveness to a lack of activating receptors such as CD14, FcaR, FcgRI and FcgRIII, complement receptors (CR) 3 and 4, and the triggering receptor expressed on myeloid cells (TREM)-1 [16,36]. It was also suggested that such cells did not express TLR; however, more recent work has shown that human intestinal Mjs can express many TLR [37] and our own work shows that murine colonic Mjs uniformly express TLR2. As a result, it seems that intestinal Mjs have a functional blockade in the downstream signalling of TLR.…”
Section: How Are Intestinal Macrophages Kept Inert?mentioning
confidence: 99%
See 1 more Smart Citation
“…Smad3/IκBα signalling pathway is the main downstream mediator of TGFβ1 and responsible for its anti‐inflammatory effect 11. TGFβ1 has been reported to express in vascular wall, including endothelial cells, vascular smooth muscle cells, monocytes/macrophages, regulatory T cells and myofibroblasts 16.…”
Section: Discussionmentioning
confidence: 99%
“…Transforming growth factor beta 1 (TGFβ1) is a pleiotropic growth factor and potentially modulates the function of cells that contribute to atherosclerotic formation, such as vascular smooth muscle cells, endothelial cells, T cells and macrophages. Smad3/IκBα signalling is the main downstream mediator and responsible for the anti‐inflammatory effects of TGFβ1 11. The enhancement of Smad3 phosphorylation and nuclear expression can increase NF‐κB inhibitor alpha (IκBα) degradation and nuclear factor‐kappa B (NF‐κB) activation, which thus promotes the inflammatory reaction and atherosclerosis 12…”
Section: Introductionmentioning
confidence: 99%